2016
DOI: 10.3961/jpmph.16.035
|View full text |Cite
|
Sign up to set email alerts
|

The Association Among Individual and Contextual Factors and Unmet Healthcare Needs in South Korea: A Multilevel Study Using National Data

Abstract: ObjectivesThe objective of this study is to investigate associations between contextual characteristics and unmet healthcare needs in South Korea after accounting for individual factors.MethodsThe present study used data from the 2012 Korean Community Health Survey (KCHS) of 228 902 adults residing within 253 municipal districts in South Korea. A multilevel analysis was conducted to investigate how contextual characteristics, defined by variables that describe the regional deprivation, degree of urbanity, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 28 publications
6
18
0
Order By: Relevance
“…For instance the degree of urbanity at county level, bearing in mind some counties are more urbanised than others and the rural urban disparities in Kenya [53]. This is consistent with studies elsewhere [54], moreover this study also noted a positive significant association between urban residence and cost-related unmet need. This confirms that place(region) does influence health seeking behaviour, like in this case of unmet need due to cost [55,56].…”
Section: Discussionsupporting
confidence: 90%
“…For instance the degree of urbanity at county level, bearing in mind some counties are more urbanised than others and the rural urban disparities in Kenya [53]. This is consistent with studies elsewhere [54], moreover this study also noted a positive significant association between urban residence and cost-related unmet need. This confirms that place(region) does influence health seeking behaviour, like in this case of unmet need due to cost [55,56].…”
Section: Discussionsupporting
confidence: 90%
“…Gender (female), lower education level, rural residents, lowest household income, poor self-reported health status, and often stress awareness increased the probability of unmet medical needs. This result is consistent with that of a previous study that analyzed factors that are related to unmet medical needs caused by financial burden [ 10 ]. Furthermore, Kim et al [ 8 ] reported that lower education level is associated with higher odds of unmet medical needs.…”
Section: Discussionsupporting
confidence: 93%
“…Although the association between chronic diseases and unmet medical needs was not significant in this study, a previous study showed that the crude relative risk for dying was 1.79 in elderly individuals who had unmet medical needs among those who suffered from two or more chronic conditions [ 11 ]. As result, the strongest predictor of unmet medical needs was self-reported health status, a finding supported by prior studies [ 6 , 10 ].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Accordingly, it can be assumed that elderly individuals in regions with serious neighborhood deprivation, increasingly experience inequalities in health care accessibility [17,18]. The association between neighborhood deprivation and unmet health care needs has been investigated in the general adult population [1,1921] but not in the elderly population.…”
Section: Introductionmentioning
confidence: 99%